Simulations on vibration mode and distribution of shear stress for icing aluminum plate excited by ultrasonic vibration - Wenfeng Guo; Xiaoyu Dong; Yan Li; Yingwei Zhang; Lei Shi; De Tian (Advances in Mechanical Engineering, 2020)
Some equipment have low efficiencies and safety when their surfaces are covered with ice, such as wind turbine and airplane, so de-bonding ice on such kind of equipment surface is necessary. In this article, the ultrasonic de-icing method based on icing aluminum plate is researched by finite element method. First, the natural frequency of icing aluminum plate changing with thickness of ice is simulated by modal analysis. Then, the distributions of shear stresses at the interface between aluminum plate and ice layer changing with excitation frequencies are simulated by harmonic analysis. Second, the shear stress and de-icing area influenced by the size of piezoelectric ceramic and excitation voltage are analyzed. The simulation results show that there is lowest natural frequency with optimum thickness of ice layer used to de-bond ice for ultrasonic de-icing system. The optimum distribution law of shear stress at the interface between ice layer and aluminum is decided. In this condition, the shear stress and de-icing area increase along with the excitation voltage. However, the de-icing area increases slowly. All the simulation results lay a theoretical foundation for future experiments and application of ultrasonic de-icing.